(untitled) (Contemporary Mathematics, 2024)
In this article, we study a mathematical model of the chlamydia infection caused by sexual contact. To analyze this model, we combine the homotopy perturbation Laplace transform technique with the fractional order formulation in the Caputo sense. This article illustrates the increased degree of freedom that fractional derivative models allow to investigate disease dynamics for a given data set and to highlight memory effects. The existence, singularity, and consistency of the problem are also examined in the research. The unique parameter estimation for each value of the noninteger order makes this study more useful.